An inverted in vitro triple culture model of the healthy and inflamed intestine: Adverse effects of polyethylene particles. (December 2021) - Busch, Mathias; Kämpfer, Angela A.M.; Schins, Roel P.F.
Abstract: As environmental pollution with plastic waste is increasing, numerous reports show the contamination of natural habitats, food and drinking water with plastic particles in the micro- and nanometer range. Since oral exposure to these particles is virtually unavoidable, health concerns towards the general population have been expressed and risk assessment regarding ingested plastic particles is of great interest. To study the intestinal effects of polymeric particles with a density of <1 g/cm³ in vitro, we spatially inverted a triple culture transwell model of the healthy and inflamed intestine (Caco-2/HT29-MTX-E12/THP-1), which allows contact between buoyant particles and cells. We validated the inverted model against the original model using the enterotoxic, non-steroidal anti-inflammatory drug diclofenac and subsequently assessed the cytotoxic and pro-inflammatory effects of polyethylene (PE) microparticles. The results show that the inverted model exhibits the same distinct features as the original model in terms of barrier development and inflammatory parameters. Treatment with 2 mM diclofenac causes severe cytotoxicity, DNA damage and complete barrier disruption in both models. PE particles induced cytotoxicity and pro-inflammatory effects in the inverted model, which would have remained undetected in conventional in vitro approaches, as no effect was observed in non-inverted control cultures. Graphical abstract: Image 1 Highlights: The inverted model exhibits comparable characteristics to the original. The NSAID diclofenac is a suitable chemical control for enterotoxicity PE effects are exclusive to the inverted model. High concentrations of PE particles cause cytotoxic effects. High concentrations of PE particles induce an increase in IL-8 secretion.